Proteção contra leptospirose induzida por LipL32 coadministrada ou fusionada à LTB - Grassmann, André Alex (2011)
Leptospirosis is an infectious disease that affects humans, wild and domestic animals worldwide. Pathogenic spirochetes from the Leptospira genus are the causative agents of this zoonosis. The several Leptospira species have noted antigenic diversity, even within the same species. This is the main reason current bacterin vaccines have limitations, such as adverse effects and short term immunity, restricting their use in human populations. The need for effective leptospirosis vaccines promoted studies on characterization of new vaccine candidates. The 32 kDa outer membrane lipoprotein, LipL32, is the most abundant protein in the whole leptospira proteome, it is conserved in all pathogenic serovars and absent in saprophytes. This protein is immunogenic and able to bind to mammalian extracellular matrix. However, LipL32 subunit vaccines did not protect animals against challenge. In an attempt to solve this, we use LipL32 fused and coadministered with B subunit of the Escherichia coli heat-labile enterotoxin (LTB) to enhance the immune response. LTB is a non-toxic molecule with immunoestimulatory and immunomodulatory properties. The recombinant proteins rLTB, rLipL32 and rLTB::LipL32 were expressed in E. coli, purified and characterized. Female hamsters were distributed in groups as follows: rLTB; rLTB+rLipL32; rLTB::LipL32, homologous bacterin; PBS. The serum from each animal was collected for humoral immune response determination by ELISA. The animals were challenged with 5×LD50 dose of Leptospira interrogans strain Fiocruz L1-130. Both treatments induced high titers of anti-rLipL32 antibodies. The rLTB+rLipL32 and rLTB::LipL32 treatments afforded significant protective response upon challenge, when compared to control groups (p<0.05). No prior study with leptospirosis had used LTB as the adjuvant, or fused antigens in an attempt to control this disease. Furthermore, this is the first report of a protective subunit vaccine using rLipL32 as the antigen, and an important contribution towards the development of improved leptospirosis vaccines.